2023
DOI: 10.1021/acs.est.2c08010
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of Microplastics in the Arctic Sea Ice Alga Melosira arctica, a Vector to Ice-Associated and Benthic Food Webs

Abstract: Plastic pollution has become ubiquitous with very high quantities detected even in ecosystems as remote as Arctic sea ice and deep-sea sediments. Ice algae growing underneath sea ice are released upon melting and can form fast-sinking aggregates. In this pilot study, we sampled and analyzed the ice algaeMelosira arcticaand ambient sea water from three locations in the Fram Strait to assess their microplastic content and potential as a temporary sink and pathway to the deep seafloor. Analysis by μ-Raman and flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Because this MP release and the ice-edge bloom occur simultaneously and in the same place, some concern has arisen about the intake of MPs by organisms 11 . A recent report described high levels of MPs in Arctic sea ice algae 19 .…”
Section: Introductionmentioning
confidence: 97%
“…Because this MP release and the ice-edge bloom occur simultaneously and in the same place, some concern has arisen about the intake of MPs by organisms 11 . A recent report described high levels of MPs in Arctic sea ice algae 19 .…”
Section: Introductionmentioning
confidence: 97%
“…Although our dawning awareness of plastics' downsides developed slowly, it has culminated in a current flood of studies underscoring these risks [4][5][6][7][8][9][10]. Plastic pollution has now been found throughout the lithosphere, hydrosphere, atmosphere, cryosphere, and biosphere [11][12][13][14][15]. Although estimates vary, over 170 trillion pieces now litter the ocean [16], forming a global "plastic smog" with its own microbial ecosystem or "plastisphere" [14,17].…”
Section: Introductionmentioning
confidence: 99%
“…Plastic pollution has now been found throughout the lithosphere, hydrosphere, atmosphere, cryosphere, and biosphere [11][12][13][14][15]. Although estimates vary, over 170 trillion pieces now litter the ocean [16], forming a global "plastic smog" with its own microbial ecosystem or "plastisphere" [14,17]. Another recent study [18] determined that the annual input of new plastics into the ocean is, at 500 kilotons, slightly less than previously estimated, but nonetheless concluded that the residence time of plastics is greater than formerly thought, such that plastics persist longer and, if not removed, have more time to break and spread.…”
Section: Introductionmentioning
confidence: 99%
“…Floating low-density microplastic (MP) particles are perceived by living organisms as a food source, which is a serious risk to them and can lead to their death. Hundreds of publications have documented the impact of plastic debris on the marine ecosystem (e.g., [4][5][6][7][8][9]). In addition, the physical and chemical properties of microplastics contribute to the adsorption of contaminants on the surface of particles.…”
Section: Introductionmentioning
confidence: 99%
“…Measurement data indicate that microplastics are found in different regions of the world's oceans, from equatorial to polar regions, from the surface to sediment layer [10]. Although assessing pollution transport in Arctic waters is challenging due to the inaccessibility of the region and the lack of permanent observations, plastic pollution has been detected in sea ice [11][12][13][14], water masses [15][16][17][18], deep-sea sediments [19,20], and in ecosystems [5,9,21]. In addition to local sources (fishery, marine industrial activities, and wastewater), significant sources of plastic include remote regions at lower latitudes, from which pollution is transferred to the Arctic by ocean currents, atmospheric flows, and rivers.…”
Section: Introductionmentioning
confidence: 99%